Ocular Findings in a Case of Trisomy 18 With Variant of Dandy-Walker Syndrome - Fong-Fong Lim; Yan-Yan Ng; Jui-Ming Hu; Suh-Jen Chen; Pen-Hua Su; Jia-Yuh Chen (Elsevier, 2010)
Trisomy 18 is the second most common chromosomal syndrome and has multiple dysmorphic features. However, ocular findings in trisomy 18 are rarely reported. Retinal folds are the most common ocular finding described to date, although retinal hypopigmentation, dysplasia, and areas of hemorrhage and gliosis are also found in trisomy 18. Dandy-Walker syndrome is a brain malformation that has been reported in association with numerous chromosomal abnormalities, although it has rarely been reported in association with trisomy 18. Here, we present a case of trisomy 18 with ocular pathology and variant of Dandy-Walker syndrome, a combination that has not previously been reported.